2018
DOI: 10.1038/s41375-018-0163-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of immunoparesis in newly diagnosed myeloma and its impact on progression-free and overall survival in both old and recent myeloma trials

Abstract: We measured immunosuppression at myeloma diagnosis and assessed the impact on survival in 5826 UK myeloma trial patients. Polyclonal immunoglobulin levels were below normal in 85% of patients and above normal in only 0.4% of cases for IgA, 0.2% for IgM and no cases for IgG. Immunoparesis had a greater impact in recent trials: median overall survival (OS) was up to 3 years longer for patients without immunoparesis compared to the old trials, less than 1 year longer. Median progression-free survival (PFS) was 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 32 publications
4
57
1
Order By: Relevance
“…Immunoparesis has been suggested as an unfavorable prognosis in newly diagnosed MM patients . To evaluate whether immunoparesis has significant importance for survival, we further analyzed the survival of patients after the diagnosis of pneumonia or sepsis (Figures and ).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Immunoparesis has been suggested as an unfavorable prognosis in newly diagnosed MM patients . To evaluate whether immunoparesis has significant importance for survival, we further analyzed the survival of patients after the diagnosis of pneumonia or sepsis (Figures and ).…”
Section: Resultssupporting
confidence: 86%
“…Immunoparesis has been suggested as an unfavorable prognosis in newly diagnosed MM patients. [12][13][14] To evaluate whether immunoparesis has significant importance for survival, we further analyzed the survival of patients after the diagnosis of pneumonia or sepsis (Figures 3 and 4). We found no significant difference in the survival of patients with immunoparesis or without quantitative immunoparesis of 25% after a diagnosis of pneumonia or sepsis (P = 0.18 and P = 0.95, respectively).…”
Section: Survival Of MM Patients With Immunoparesis After the Diagnmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this might be that the patients with R-ISS stage I responded well and most of them achieved CR and subsequent Ig recovery, while patients with R-ISS stage III or high risk may suffered a long time enough to cause clonal evolution and normal plasma cells might be more strongly suppressed, and thus humoral immune recovery was more difficult to occur. As support for this hypothesis, several studies have reported that patients with R-ISS stage III and adverse cytogenetic abnormalities were more likely to have suppression of Ig at diagnosis [15,16]. Further studies are needed to elucidate the mechanism of immunosuppression and the relationship between cytogenetic abnormality of MM cells and its inhibitory effects on normal plasma cells.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, most patients present with immunoparesis at diagnosis, which is shown to be another important prognostic factor associated with PFS and OS [14][15][16]. Since subsequent treatment itself induces humoral and cellular immunodeficiency, the balance between treatment intensity and immune recovery is a crucial issue for improving the long-term disease stability.…”
Section: Introductionmentioning
confidence: 99%